PENGGUNAAN ALAT PERAGA DENGAN PEMBELAJARAN LANGSUNG DALAM MENINGKATKAN MOTIVASI MENGAJAR GURU DI SMPN 2 KUBU KABUPATEN ROKAN HILIR - Baharuddin ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aims to determine whether the use of props in direct learning can increase themotivation of teachers to teach in SMPN 2 Kubu Kabupaten Rokan Hilir. Formulation of theproblem in this study is: Does the use of props to increase the motivation of teachers in teachingin SMPN 2 Kubu Kabupaten Rokan Hilir? This study was limited to Improve teacher motivationin teaching by using props in SMPN 2 Kubu Kabupaten Rokan Hilir. This research wasconducted in SMPN 2 Kubu Kabupaten Rokan Hilir. The teacher is the subject of the studyconsisted of 18 teachers. Characteristics of the teacher motivated heterogeneous, but can not besaid to be using props intensive time of learning. Based on the analysis and discussion can beconcluded that the principal aspects of activities as a facilitator to get the achievement with ascore of 25 or with a percentage of 63 of all aspects of assessment or 63% of all activities isreached. Then in the second cycle of scores obtained by 38 or by the percentage of achievementof 95% of all aspects achieved. Aspects of the teacher as participators in this study in which thefirst cycle scores obtained from the implementation of the directives by the principal to get ascore of 73 or with the percentage of achievement of 51%. Then at the second cycle level ofparticipation was 74% higher than the first cycle and with a score of 106. The implementation ofthe motivational aspect of teaching the teachers during the implementation of the directives ofthe first cycle to the second cycle, the motivation of teachers in using props tend to rise. Whereinif the first cycle obtain the percentage of achievement of 64% in both categories, then the secondcycle obtain a percentage of 88% or with a very good category.